The role of intestinal microbes on intestinal barrier function and host immunity from a metabolite perspective - Fu, Yifeng; Lyu, Jin; Wang, Shuangshuang (Frontiers in Immunology, 2023)
The gut is colonized by many commensal microorganisms, and the diversity and metabolic patterns of microorganisms profoundly influence the intestinal health. These microbial imbalances can lead to disorders such as inflammatory bowel disease (IBD). Microorganisms produce byproducts that act as signaling molecules, triggering the immune system in the gut mucosa and controlling inflammation. For example, metabolites like short-chain fatty acids (SCFA) and secondary bile acids can release inflammatory-mediated signals by binding to specific receptors. These metabolites indirectly affect host health and intestinal immunity by interacting with the intestinal epithelial and mucosal immune cells. Moreover, Tryptophan-derived metabolites also play a role in governing the immune response by binding to aromatic hydrocarbon receptors (AHR) located on the intestinal mucosa, enhancing the intestinal epithelial barrier. Dietary-derived 2 This is a provisional file, not the final typeset article indoles, which are synthetic precursors of AHR ligands, work together with SCFA and secondary bile acids to reduce stress on the intestinal epithelium and regulate inflammation. This review highlights the interaction between gut microbial metabolites and the intestinal immune system, as well as the crosstalk of dietary fiber intake in improving the host microbial metabolism and its beneficial effects on the organism.